Penerapan Metode Regresi Linear Dalam Prediksi Hasil Penangkapan Ikan Pada Dinas Kelautan Dan Perikanan Provinsi Bengkulu - Gebi Andre Anto; Indra Kanedi; Rizka Tri Alinse (Jurnal Media Infotama, 2025)
Abstract— The Department of Marine and Fisheries of Bengkulu Province is one of the government agencies in Bengkulu Province. At the Department, every year data collection is carried out per semester of capture fisheries production that occurs in each regency / city in Bengkulu Province. The purpose of the research is to determine the predicted value of capture fisheries production in the coming year. The implementation of the linear regression method in predicting fishing yields at The Department of Marine and Fisheries of Bengkulu Province can help provide an estimated prediction of the amount of capture fisheries production in the following year based on the results of processing previous time series data through the Linear Regression Method. In addition, it can be used as an evaluation material for the Department of Marine and Fisheries of Bengkulu Province in making strategic plans (renstra), especially capture fisheries production. Based on the test data used, the results show that the prediction of the amount of fishing (marine fisheries) in the Regency / City of Bengkulu Province in 2024 is South Bengkulu Regency, 2726.3 Central Bengkulu Regency, 1663.62 North Bengkulu Regency, 7709.04 Kaur Regency, 8140.2 Bengkulu City, 44457.32 Muko-muko Regency, 19691.99 and Seluma Regency, 2633.8. It can be seen that the highest number of fishing products is Bengkulu City and the least is Central Bengkulu Regency from the results of prediction analysis using the linear regression method. Keywords: Linear Regression Method, Prediction, Fishing Result.